A Self‐Powered Angle Sensor at Nanoradian‐Resolution for Robotic Arms and Personalized Medicare. Issue 32 (30th June 2020) - Wang, Ziming; An, Jie; Nie, Jinhui; Luo, Jianjun; Shao, Jiajia; Jiang, Tao; Chen, Baodong; Tang, Wei; Wang, Zhong Lin
Abstract: As the dominant component for precise motion measurement, angle sensors play a vital role in robotics, machine control, and personalized rehabilitation. Various forms of angle sensors have been developed and optimized over the past decades, but none of them would function without an electric power. Here, a highly sensitive triboelectric self‐powered angle sensor (SPAS) exhibiting the highest resolution (2.03 nano‐radian) after a comprehensive optimization is reported. In addition, the SPAS holds merits of light weight and thin thickness, which enables its extensive integrated applications with minimized energy consumption: a palletizing robotic arm equipped with the SPAS can precisely reproduce traditional Chinese calligraphy via angular data it collects. In addition, the SPAS can be assembled in a medicare brace to record the flexion/extension of joints, which may benefit personalized orthopedic recuperation. The SPAS paves a new approach for applications in the emerging fields of robotics, sensing, personalized medicare, and artificial intelligence. Abstract : Sensing angular information via the most energy‐efficient method is vitally important. After systematic optimization, a triboelectric self‐powered angle sensor provides high‐quality sensing signals while itself needing neither electric power supply nor a signal‐amplification module. In addition, its feasibility is proved by practical application in a robotic arm, precisely duplicating traditional Chinese calligraphy as well as medical brace monitoring joint motions.